2010
DOI: 10.1051/ocl.2010.0327
|View full text |Cite
|
Sign up to set email alerts
|

Challenges when developing omega-3 enriched foods

Abstract: Due to the polyunsaturated nature of omega-3 fatty acids, lipid oxidation is a major challenge when developing omega-3 enriched foods. In multiphase food systems, several factors can affect lipid oxidation and efficacy of antioxidants, added to prevent lipid oxidation. This review discusses the influence of important factors such as oil quality, delivery systems for omega-3 fatty acids, processing conditions, composition of the food matrix on lipid oxidation in different omega-3 enriched foods (milk, yoghurt, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…. others 2003, 2013;Frankel 2005;Jacobsen and others 2008;Jacobsen 2010aJacobsen , 2010bWaraho and others 2011a). These studies have notably emphasized that the interfacial region, which is the contact region between the oil phase and the aqueous phase, represents a particularly critical area in the system with regard to the development of lipid oxidation.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…. others 2003, 2013;Frankel 2005;Jacobsen and others 2008;Jacobsen 2010aJacobsen , 2010bWaraho and others 2011a). These studies have notably emphasized that the interfacial region, which is the contact region between the oil phase and the aqueous phase, represents a particularly critical area in the system with regard to the development of lipid oxidation.…”
Section: Introductionmentioning
confidence: 93%
“…Since the late 1980s, substantial work has further been performed with respect to lipid oxidation in emulsions and, more generally, in multiphase systems. The main compositional and structural factors that influence lipid oxidation in emulsions and food formulations have been deduced from studies performed on more or less simplified model emulsions (Fritsch ; Coupland and McClements ; McClements and Decker ; Genot and others , ; Frankel ; Jacobsen and others ; Jacobsen , ; Waraho and others ). These studies have notably emphasized that the interfacial region, which is the contact region between the oil phase and the aqueous phase, represents a particularly critical area in the system with regard to the development of lipid oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the fruit consists of both hydrophilic and lipophilic metal chelating properties, which may decrease metal-catalyzed radical reactions such as lipid peroxidation. Jacobsen [35] reported that scavenging of free lipid radicals, peroxyl and alkoxyl radicals is the most important mechanism for preventing lipid oxidation. Furthermore, MS and DS showed near to similar as well as the highest total antioxidant capacity followed by CS and ES, Figure 1(D).…”
Section: Downloaded By [Mcmaster University] At 20:34 10 October 2015mentioning
confidence: 99%
“…Thus, in this study, rancid (a somewhat heavy aromatic characteristic of old, oxidized, decomposing fat and oil) and painty (the aromatic associated with rancid oil and fat, typically in the late stages of rancidity) were chosen to be key attributes to determine the shelf life of the products. Rancid and other off‐note characteristics from lipid degradation in food often have low threshold values and are easily perceived by human even at low concentration (Jacobsen, ; Skibsted, Mikkelsen, & Bertelsen, ; W'sowicz et al., ). Rancidity‐related sensory attributes also have been used as critical descriptors for shelf life estimation for several products, such as extruded pet food (Chanadang et al., ), avocado paste (Jacobo‐Velázquez & Hernández‐Brenes, ), and spray‐dried fish oil powder (Keogh et al., ).…”
Section: Resultsmentioning
confidence: 99%